Influence of varying seed rates and integrated nutrient management on performance of direct-seeded hybrid rice (Oryza sativa) - MEENA, HEMRAJ; SINGH, M K; RANI, MEENA (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted during kharif season of 2016 and 2017 in direct-seeded hybrid rice (Oryza sativa L.) under varying seeding rates and integrated nutrient management. The experiment consisted of three seed rates (16, 20 and 24 kg/ha) and five nutrient management, viz. 100% RDF through inorganic fertilizer, 100% RDF through inorganic fertilizer + ZnSO4.7H2O 25 kg/ha fb 0.2% FeSO4 and 0.2% Borax foliar spray at 20 and 40 DAS, 75% RDN through inorganic fertilizer + 25% N through FYM, 50% RDN through inorganic fertilizer + 50% N through FYM, 75% RDN through inorganic fertilizer + 25% N through vermicompost. Seed rate of 20 kg/ha recorded superior performance with respect to number of tillers/m2, dry matter accumulation, LAI, SPAD value, grain and straw yields and nutrient uptake as compared to seed rate of 16 and 24 kg/ha. Amongst integrated nutrient management treatments, application of 50% RDN by urea + 50% N by FYM recorded better performance with respect to tillers/ m2, dry matter accumulation, LAI, SPAD value, grain and straw yields and nutrient uptake while 100% RDF through inorganic fertilizer recorded lowest growth and yield.